Developmental disorders with intellectual disability driven by chromatin dysregulation: Clinical overlaps and molecular mechanisms. Issue 2 (21st May 2018) - Larizza, L.; Finelli, P.
Abstract : Advances in genomic analyses based on next‐generation sequencing and integrated omics approaches, have accelerated in an unprecedented way the discovery of causative genes of developmental delay (DD) and intellectual disability (ID) disorders. Chromatin dysregulation has been recognized as common pathomechanism of mendelian DD/ID syndromes due to mutation in genes encoding chromatin regulators referred as transcriptomopathies or epigenetic disorders. Common to these syndromes are the wide phenotypic breadth and the recognition of groups of distinct syndromes with shared signs besides cognitive impairment, likely mirroring common molecular mechanisms. Disruption of chromatin‐associated transcription machinery accounts for the phenotypic overlap of Cornelia de Lange with KBG and with syndromes of the epigenetic machinery. The genes responsible for Smith‐Magenis‐related disorders act in interconnected networks and the molecular signature of histone acetylation disorders joins Rubinstein‐Taybi‐related syndromes. Deciphering pathway interconnection of clinically similar ID syndromes may enhance search of common targets useful for developing new therapeutics. Abstract :